OP0181 New Autoantibodies as Biomarkers for Early and Seronegative Rheumatoid Arthritis. (23rd January 2014) - De Winter, L.; Hansen, W.; Geusens, P.; Vanhoof, J.; Lenaerts, J.; Langenaken, C.; Stinissen, P.; Somers, V.
Abstract : Background: Approximately one third of rheumatoid arthritis (RA) patients test negative on the current diagnostic biomarkers rheumatoid factor (RF) and antibodies directed against cyclic citrullinated peptides (ACCP) leading to a difficult and delayed diagnosis. In a previous study 14 novel candidate biomarkers for RA were identified 1 . Objectives: The four most promising autoantibody markers were further validated in early and seronegative RA patients. Methods: By means of peptide ELISA antibody reactivity against the four candidate biomarkers (UH-RA.1, UH-RA.9, UH-RA.14 and UH-RA.21) was measured in a first cohort of 127 RA patients, 97 healthy controls and 87 rheumatic controls including psoriatic arthritis, ankylosing spondylitis, osteoarthritis and Sjögren's syndrome patients. Furthermore, a validation cohort of 166 RA patients was screened. Amongst the 293 RA patients 24% could not be identified using the current diagnostic biomarkers RF and ACCP. In addition, the autoantibody response against the four biomarkers was evaluated in 52 early RA patients included in this study population. Results: In the first cohort, the results demonstrated a sensitivity for UH-RA.1, UH-RA.9, UH-RA.14 and UH-RA.21 of 8.7%, 1.6%, 4.7% and 18.1% with associated specificity for RA of 95%, 98%, 100% and 89% respectively. Combined into one biomarker panel a sensitivity of 30% was reached with 83% specificity for RA. This sensitivity was confirmed in the validation cohort of 166 RA patients in which 34% tested positive on the biomarkers. Furthermore, antibody reactivity against the biomarker panel was associated with increased CRP levels (p=0.034). Importantly, our biomarkers enabled the identification of 26% of the RF-negative ACCP-negative subpopulation, thereby closing the serological gap from 24% to 17% in this study population. Of the 69 seronegative RA patients, 7% and 17% were identified by UH-RA.1 and UH-RA.21 respectively. Moreover, our biomarkers were shown to be present in early disease stages as no less than 37% of early RA patients tested positive on the biomarkers: 12% was positive for UH-RA.1 and 27% was positive for UH-RA.21. Besides, three out of six early and seronegative patients were identified by measuring the antibody response against UH-RA.1 and UH-RA.21. In the early RA subpopulation, antibody reactivity against UH-RA.1 was associated with lower disease activity (DAS28; p=0.016), a negative RF status (p=0.033) and visual analogue score (p=0.016). Conclusions: The detection of antibody reactivity against our candidate biomarkers in 37% of early and 26% of seronegative RA patients implies that these biomarkers can be of additional value to the current diagnostic biomarkers for RA, with most promising results for UH-RA.1 and UH-RA.21. Our biomarkers may therefore contribute to an improved early diagnosis of RA. Significant associations with inflammatory factors and disease activity indicate an important prognostic potential as well. References: Somers K et al. J Autoimmun. 2011 Feb;36(1):33-46. Disclosure of Interest: None Declared